A new SO2 probe ZSO targeting VDBP inhibits high glucose induced endothelial cell senescence and calcification - Zhang, Yangyang; Yan, Xiaomeng; Dong, Xinyu; Zhao, Congyao; Chi, Xiaohui; Zhao, Baoxiang; Miao, Junying; Lin, Zhaomin (Frontiers in Physiology, 2026)
IntroductionVitamin D binding protein (VDBP) serves as a key biomarker for vascular injury, offering important applications in both diagnosis and prognosis. However, its precise functional role remains incompletely understood.MethodsWe investigated the compound ZSO as a VDBP-interacting compound conferring potent anti-senescence effects. Given that endothelial senescence and calcification drive vascular aging, processes accelerated by high glucose. We assessed the impact of ZSO in vitro using high glucose-induced vascular endothelial cell models of senescence and calcification and in vivo using a db/db mouse model of vascular aging and calcification.ResultsZSO treatment markedly alleviated high glucose-induced endothelial cell senescence and calcification in vitro and suppressed vascular aging and calcification in db/db mice in vivo. Mechanistic investigations revealed that high glucose-induced vascular endothelial senescence and calcification were accompanied by upregulated VDBP protein levels. The compound ZSO bound to pathologically elevated VDBP in senescent endothelial cells and db/db mice, triggering its ubiquitin-mediated proteasomal degradation without altering transcriptional regulation.DiscussionThis study identifies ZSO as a novel small molecule that inhibits endothelial senescence and calcification, and establishes its role in directly targeting VDBP to promote degradation. Furthermore, our findings underscore the critical role of VDBP in vascular aging and calcification and suggest its potential utility as a biomarker for diabetic vascular complications.